STRENGTHENING THE COMMUNITY ECONOMY THROUGH USE OF OIL WASTE AND ECOPRINT TRAINING FOR SME INNOVATION IN PASIR DISTRICT HORSE - Aminda, Renea Shinta; Darmawan, Ahmad; Azzahra, Ananda Puteri; Julianti, Anisa; Yuliasari, Rahma; Hidayah, Wafa (LPPM Univ. Ibn Khaldun Bogor, 2023)
Pasir Kuda Village was assigned as the location for KKN group 02 at Ibn Khaldun University, Bogor. The focus of the work program isStrengthening the community economy throughMSMEs in the surrounding community formmmore andincrease the competitiveness of their products. The duration of this activity is 25 days, from 7-31 August 2023 in RW 04, Pasir Kuda Village, West Bogor. Students use their creativity and knowledge to make real contributions to society through innovative solutions. They also involve 6th grade elementary school students in training to hone their creativity and skills. The research methods used are surveys and case studies with a descriptive approach. Primary data was obtained through direct observation and interviews with related informants, while secondary data was collected from sources such as history, profiles, regulations, policies and documentation of activities in RT04 RW03 and RT02 RW04, Pasir Kuda Village. The implementation includes data collection techniques, field observation, direct interviews, as well as documentation as the main medium for obtaining the required information. There are two main stages, namely training in processing used cooking oil into aromatherapy candles and implementing ecoprint techniques at SD Negeri Cibalagung 04